Renovated controller designed by genetic algorithms. - Lin, Tzu-Kang (Earthquake engineering & structural dynamics.)
A novel smart control system based on genetic algorithms (GAs) is proposed in this paper. The system is comprised of three parts: the fiber Bragg grating (FBG) sensor-based sensing network for structural health monitoring, the GA-based location optimizer for sensor arrangement, and the GA-based controller for vibration mitigation under external excitation. To evaluate the performance of the proposed system, an eight-story steel structure was designed specifically to represent a structure with large degrees of freedom. In total 16 FBG sensors were deployed on the structure to implement the concept of a reliable sensing network, and to allow the structure to be monitored precisely under any loading. The advantage of applying a large amount of information from the sensing system is proven theoretically by the GA-based location optimizer. This result greatly supports the recent tendency of distributing sensors around the structure. Two intuitive GA-based controllers are then proposed and demonstrated numerically. It is shown that the structure can be controlled more effectively by the proposed GA-strain controller than by the GA-acceleration controller, which represents the traditional control method. A shaking table test was carried out to examine the entire system. Experimental verification has demonstrated the feasibility of using this system in practice.